2018
DOI: 10.1016/j.ajo.2018.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Effects of Hormone Therapy on Incident Open-Angle Glaucoma in a Randomized Trial

Abstract: Analysis suggests that HT containing estrogen, but not a combination of estrogen and progesterone, reduces the risk of incident OAG among African-American women. Further investigation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…In the WHI, ET reduced intraocular pressure in postmenopausal women and mitigated the risk for open-angle glaucoma in Black women 146,147 . Similar effects were not seen for EPT 148 .…”
Section: Skin Hair and Special Sensesmentioning
confidence: 78%
“…In the WHI, ET reduced intraocular pressure in postmenopausal women and mitigated the risk for open-angle glaucoma in Black women 146,147 . Similar effects were not seen for EPT 148 .…”
Section: Skin Hair and Special Sensesmentioning
confidence: 78%
“…Recently, several lines of evidence have indicated that E2 influences the onset of POAG in women (Hulsman et al, 2001;Vajaranant et al, 2018). In the population-based Rotterdam Study, it was found that women who experienced menopause at <45 years of age had a significantly higher risk of POAG than women who experienced menopause at >50 years of age (Hulsman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the population-based Rotterdam Study, it was found that women who experienced menopause at <45 years of age had a significantly higher risk of POAG than women who experienced menopause at >50 years of age (Hulsman et al, 2001). In addition, a randomized trial of hormone therapy with 25,535 women and a retrospective longitudinal cohort study that enrolled 152,163 postmenopausal women suggested that hormone therapy consisting of E2 only reduced the incidence of open-angle glaucoma (Newman-Casey et al, 2014;Vajaranant et al, 2018). Other studies have suggested that decreased E2 might be associated with POAG pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 7 studies examining PMH use and risks of OAG. One study was an ancillary study within a placebo-controlled RCT, 17 2 studies 14 , 18 were cohort studies ( Table 9 ), and 4 studies 19 , 22 , 24 , 34 were cross-sectional population studies involving a total of 18 152 participants with 853 cases of OAG ( Table 10 ).…”
Section: Resultsmentioning
confidence: 99%